Automatic and improved radiometric correction of Landsat imagery using reference values from MODIS surface reflectance images - Pons, X; Pesquer, L; Cristóbal, J; González-Guerrero, O (International Journal of Applied Earth Observation and Geoinformation, 2014)
Radiometric correction is a prerequisite for generating high-quality scientific data, making it possible to discriminate between product artefacts and real changes in Earth processes as well as accurately produce land cover maps and detect changes. This work contributes to the automatic generation of surface reflectance products for Landsat satellite series. Surface reflectances are generated by a new approach developed from a previous simplified radiometric (atmospheric+topographic) correction model. The proposed model keeps the core of the old model (incidence angles and cast-shadows through a digital elevation model [DEM], Earth–Sun distance, etc.) and adds new characteristics to enhance and automatize ground reflectance retrieval. The new model includes the following new features: (1) A fitting model based on reference values from pseudoinvariant areas that have been automatically extracted from existing reflectance products (Terra MODIS MOD09GA) that were selected also automatically by applying quality criteria that include a geostatistical pattern model. This guarantees the consistency of the internal and external series, making it unnecessary to provide extra atmospheric data for the acquisition date and time, dark objects or dense vegetation. (2) A spatial model for atmospheric optical depth that uses detailed DEM and MODTRAN simulations. (3) It is designed so that large time-series of images can be processed automatically to produce consistent Landsat surface reflectance time-series. (4) The approach can handle most images, acquired now or in the past, regardless of the processing system, with the exception of those with extremely high cloud coverage. The new methodology has been successfully applied to a series of near 300 images of the same area including MSS, TM and ETM+ imagery as well as to different formats and processing systems (LPGS and NLAPS from the USGS; CEOS from ESA) for different degrees of cloud coverage (up to 60%) and SLC-off. Reflectance products have been validated with some example applications: time series robustness (for a pixel in a pseudoinvariant area, deviations are only 1.04% on average along the series), spectral signatures generation (visually coherent with the MODIS ones, but more similar between dates), and classification (up to 4 percent points better than those obtained with the original manual method or the CDR products). In conclusion, this new approach, that could also be applied to other sensors with similar band configurations, offers a fully automatic and reasonably good procedure for the new era of long time-series of spatially detailed global remote sensing data.
Keywords: Landsat; MODIS; Pseudoinvariant area; Radiometric correction

Expansion of the aphid Myzocallis (Lineomyzocallis) walshii (Monell) on the red oak Quercus rubra, and adaptation of local parasitoids in the northeastern Iberian Peninsula (Hom., Aphididae, Calaphidinae; Hym., Braconidae, Aphidiinae) - Pons, X; Lumbierres, B; Starý, P (Journal of Pest Science, 2005)
An ongoing expansion of Myzocallis (L.) walshii (Monell) in the NE Iberian Peninsula was detected. The aphid species was recorded in Catalonia, Andorra and Navarra. Adaptation of local native parasitoids (at least Trioxys pallidus Haliday and T. tenuicaudus Stary´) to the new immigrant was documented, together with background information on their host range in the native environments. The detection of parasitoids of M. walshii is the ﬁrst published evidence in Europe. The new evidence for M. walshii in the NE Iberian Peninsula also supports the warning of the expansion of the aphid as a pest of Quercus rubra over Europe.
Keywords: Aphids; Myzocallis walshii; Parasitoids; Quercus sp.; Trioxys pallidus; Trioxys tenuicaudus

Influence of fire severity on plant regeneration by means of remote sensing imagery - Díaz-Delgado, R; Lloret, F; Pons, X (International Journal of Remote Sensing, 2003)
In this paper we analyse the interactions between fire severity (plant damage) and plant regeneration after fire by means of remote sensing imagery and a field fire severity map. A severity map was constructed over a large fire (2692 ha) occurring in July 1994 in the Barcelona province (north-east of Spain). Seven severity classes were assigned to the apparent plant damage as a function of burning intensity. Several Landsat TM and MSS images from dates immediately before and after the fire were employed to monitor plant regeneration processes as well as to evaluate the relationship with fire severity observed in situ . Plant regeneration was monitored using NDVI measurements (average class values standardized with neighbour unburned control plots). Pre-fire NDVI measurements were extracted for every plant cover category (7), field fire severity class (7), and spatial cross-tabulation of both layers (33) and compared to post-fire values. NDVI decline due to fire was positively correlated with field fire severity class. Results show different patterns of recovery for each dominant species, severity class and combination of both factors. For all cases a significant negative correlation was found between damage and regeneration ability. This work leads to a better understanding of the influence of severity, a major fire regime parameter on plant regeneration, and may aid to manage restoration on areas burned under different fire severity levels.
doi: 10.1080/01431160210144732
Keywords: dominant species (voyant); fire severity; NDVI; plant damage; plant regeneration